THE EFFECT OF FIQH AN-NISAA ON THE PREVENTION OF STUDENTS’ DEVIANT BEHAVIOR AT ATHIRAH ISLAMIC HIGH SCHOOL BONE - Jumardi J (IAIN Bone, 2022)
Fiqh An-nisaa has an influence in increasing the religious value of students who are just with the goals of the national education system and the goals of Islamic education. Which in substance is the ability to shape students into better individuals and avoid acts that are prohibited by religion (deviant). Therefore, there is a significant influence of the fiqh an-nisaa’s learning process on the prevention of deviant behavior of students at Athirah Islamic High School Bone which shows a probability value of 0.005 which is smaller than = 0.05 which can be accepted as an influential one. This means learning Fiqh An-Nisaa able to increase religious values and be able to minimize the occurrence of deviant behavior.